Giant: Elizabeth Taylor, Rock Hudson, James Dean, Edna Ferber, and the Making of a Legendary American Film - Graham, Don, 1940- (New York : St. Martins Press, 2018)
"A larger-than-life narrative of the making of the classic film, marking the rise of America as a superpower, the ascent of Hollywood celebrity, and the flowering of Texas culture as mythology"--Amazon.com.
Keywords: Ferber, Edna, -- 1887-1968 -- Film and video adaptions; Stevens, George, -- 1904-1975; Giant (Motion picture); Motion pictures -- United States; History -- 20th century; Celebrities -- United States; History -- 20th century; Texas -- Social life and customs